A reverse GPS architecture for tracking and location of small objects - Andrade, T.
A novel architecture for the location and tracking of small objects using a GPS-like architecture is described. Unlike the conventional GPS system, the proposed architecture places the emitters at the objects to be tracked and the receivers at fixed (earth) stations, so that the emitters can be made very simple and most of the intelligence of the system is located at the receivers. Due to the very low signal-to-noise ratio of the received signals, signal recovery techniques based on correlation and codification, similar to the ones used in spread-spectrum systems, are used in this architecture. The expected noise budget and coding techniques to be used are discussed. © 2011 IEEE.